Synthesis and properties of acetylene-containing cross-linkable triazine resin - J. L. Zhou; Y. H. Hu; J. J. Hu; N. Jiang; S. F. Deng (eXPRESS Polymer Letters)
A triazine-based functional monomer (AET) was synthesized via a nucleophilic substitution reaction between cyanuric chloride and 3-aminophenylacetylene. The comprehensive properties were superior, including simple synthesis conditions, moderate curing conditions, excellent thermal properties, and good mechanical properties of laminated composites comprised of AET and quartz fiber. The curing reaction showed high reactivity and low temperature, an activation energy of 106.33 kJ・mol–1 and cure exothermic peak between 140 and 250 °C with an enthalpy of 780 J・g–1. The decomposition temperature at 5% mass loss was 521 °C, the char yield at 800 °C was 78% and the glass transition temperature was 470 °C. Moreover, QF/P-AET laminated composite possessed good mechanical properties. The flexural strength was 364.94 Mpa and the interlaminar shear strength was 30.4 MPa at room temperature (RT); especially at 300 and 500 °C, the composite still displayed a high mechanical strength retention of up to 66 and 88, and 45 and 42%, respectively which is unachievable for cyanate and aryl acetylene resins. All above attracting properties make AET a good candidate as a matrix for high performance polymeric composite materials.